Medication Adherence Levels in Diabetes Mellitus Patients at Primary Healthcare - Abdul Aziz; Ach Fathir; Ach Faruk Alrosyidi (Academia Open, 2026)
General Background: Diabetes mellitus is a chronic non-communicable disease requiring long-term therapy, where medication adherence is essential for achieving optimal glycemic control and preventing complications. Specific Background: In primary healthcare settings such as Puskesmas Proppo Pamekasan, adherence to antidiabetic therapy remains a critical component of patient management. Knowledge Gap: However, the actual level of medication adherence among diabetes mellitus patients in this setting has not been clearly described. Aims: This study aimed to determine the level of medication adherence among patients with diabetes mellitus at UPT Puskesmas Proppo. Results: Using a descriptive quantitative approach with 30 respondents selected through purposive sampling, the findings showed that most patients were aged ≥45 years, predominantly female, and had suffered from diabetes for ≥5 years, with oral antidiabetic drugs as the main therapy. The level of medication adherence was predominantly moderate (56.7%), followed by high (23.3%) and low adherence (20.0%), indicating inconsistency in following prescribed therapy. Novelty: This study provides a localized descriptive profile of medication adherence levels and associated patient characteristics in a primary healthcare context. Implications: The findings highlight the need for continuous education, counseling, and monitoring by healthcare professionals, particularly pharmacists, to improve adherence and support optimal diabetes management outcomes. Highlights: Majority of participants were categorized in the moderate compliance group, indicating inconsistency in therapy implementation. Patient characteristics such as age, education, and disease duration were associated with adherence patterns. Continuous education and counseling are required to support consistent treatment behavior. Keywords: Diabetes Mellitus, Adherence, Medication Therapy, Patients